2017
DOI: 10.1080/15226514.2016.1267698
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of coal mine effluent generated at the Rajrappa coal mine using phytoremediation technology

Abstract: Toxicity of the effluent generated at the Rajrappa coal mine complex under the Central Coalfields Limited (CCL, a subsidiary of Coal India Limited) in Jharkhand, India was investigated. The concentrations (mg L) of all the toxic metals (Fe, Mn, Ni, Zn, Cu, Pb, Cr, and Cd) in the coal mine effluent were above the safe limit suggested by the Environmental Protection Agency (EPA 2003). Among these, Fe showed the highest concentration (18.21 ± 3.865), while Cr had the lowest effluent concentration (0.15 ± 0.014). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Floating aquatic plants cannot improve adsorption via the substrate, however, they promote adsorption process to the plant biomass. Successfully used floating aquatic plants in the treatment of mine effluents include Salvinia natans, Pistia stratiotes, Eichornia crassipes [239,288]. Submerged aquatic macrophytes like Ceratophylum demersum, Cabomba piauhyensis, Egeria densa, Myriophylum spicatum and Hydrilla verticillata are recommended to be used for the phytoremediation of mine effluents as they have shown outstanding ability to accumulate HMs in their whole body biomass [289,290].…”
Section: Phytoremediation Of Mining Effluentsmentioning
confidence: 99%
“…Floating aquatic plants cannot improve adsorption via the substrate, however, they promote adsorption process to the plant biomass. Successfully used floating aquatic plants in the treatment of mine effluents include Salvinia natans, Pistia stratiotes, Eichornia crassipes [239,288]. Submerged aquatic macrophytes like Ceratophylum demersum, Cabomba piauhyensis, Egeria densa, Myriophylum spicatum and Hydrilla verticillata are recommended to be used for the phytoremediation of mine effluents as they have shown outstanding ability to accumulate HMs in their whole body biomass [289,290].…”
Section: Phytoremediation Of Mining Effluentsmentioning
confidence: 99%
“…Similarly, two rooted macrophytes Phragmites australis and Typha angustifolia removed 14–85% Fe from municipal wastewater in hydroponic experiment (Pedescoll et al, 2015). In addition, Fe phytofilteration potential autochthonous floating macrophytes (Miretzky et al, 2004), water lettuce (Galal et al, 2018; Sarwar et al, 2019), duckweed species (Flores‐Miranda et al, 2014; Teixeira et al, 2014), Salvinia species (Lakra et al, 2017), and Typha species (Pedescoll et al, 2015) were reported.…”
Section: Remediation Of Fementioning
confidence: 99%